2018
DOI: 10.3892/ijo.2018.4616
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone-induced inhibition of miR-132 via methylation promotes TGF-β-driven progression of pancreatic cancer

Abstract: Glucocorticoids (GCs) such as dexamethasone (DEX) are administered as cancer co-treatment for palliative purposes due to their pro-apoptotic effects in lymphoid cancer and limited side effects associated with cancer growth and chemotherapy. However, there is emerging evidence that GCs induce therapy resistance in most epithelial tumors. Our recent data reveal that DEX promotes the progression of pancreatic ductal adenocarcinoma (PDA). In the present study, we examined 1 primary and 2 established PDA cell lines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…For example, Abukiwan et al . suggested that inhibition of miR-132-3p drove progression of pancreatic cancer [39]; miR-133a-5p was also found to function as a tumor suppressor in pancreatic cancer [40,41]; the group of Wang Lihua showed that miR-29b-3p decreased proliferation and mobility of pancreatic cancer by targeting SOX12 and DNMT3b [42]. Then, we further predicted 90 upstream lncRNAs of these key miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Abukiwan et al . suggested that inhibition of miR-132-3p drove progression of pancreatic cancer [39]; miR-133a-5p was also found to function as a tumor suppressor in pancreatic cancer [40,41]; the group of Wang Lihua showed that miR-29b-3p decreased proliferation and mobility of pancreatic cancer by targeting SOX12 and DNMT3b [42]. Then, we further predicted 90 upstream lncRNAs of these key miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…GR activity may underly the switch into the drug tolerant state by modifying the biological processes implicated in DTP emergence. GR activity has been demonstrated to affect such processes, including transcriptional reprograming, epigenetics, epithelial to mesenchymal transition, and TGFβ activity [23,[27][28][29] . Proposed DTP targets KDM5A and GPX4 [3,30] are like GR in their heterogeneous and reversible involvement in these processes.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that miR-132 expression is not induced by a pancreatogenic diabetes mellitus secondary to chronic pancreatitis. The connection of miR-132 expression and pancreatic cancer is controversially discussed in the literature, some studies reported a downregulation of the miR-132 expression in cancer tissue and cells 60 62 , while other studies confirmed an upregulation of miR-132 63 65 . The hepatic expression of miR-132 is reported to be upregulated after alcoholic hepatitis 66 , nonalcoholic fatty liver disease (NAFLD), hepatic steatosis 67 , as well as cholestasis 68 .…”
Section: Discussionmentioning
confidence: 99%